Emerging Mitochondria-Associated Molecular Target Therapies for Acute Myeloid Leukemia - Nakamura, Hirotaka; Minami, Yosuke; Chi, SungGi; Uchiyama, Satoshi; Nagata, Akihito; Yamauchi, Nobuhiko (Archives of Clinical and Biomedical Research, 2021)
The era of precision medicine for acute myeloid leukemia (AML) has arrived, and it is extremely important to detect actionable mutations relevant to treatment-related decision-making. However, the percentage of actionable mutations found in AML is approximately 50% at present, and therapeutic development is also needed for AML patients without such mutations. Nevertheless, recently approved drugs for AML treatment are less toxic than conventional intensive chemotherapy and can be combined with low-intensity treatments. Such combination therapies can improve prognosis, especially for elderly AML patients, who account for more than half of all AML cases. Thus, the treatment strategy for leukemia is changing drastically and showing rapid progress. In this review, we present novel mitochondria-associated molecular target therapies for AML, such as the use of BCL-2 and IDH inhibitors.